Description Gender, Age on The Incidence of Acute Respiratory Infections (ARI) at Baula Community Health Center - Elmika, Elma; Idris, Idris; Salda, Ifan Pratama (Journal of Midwifery and Nursing, 2025)
Acute Respiratory Tract Infection (ARI) is a major health problem worldwide associated with high morbidity and mortality. In Indonesia, ARI always ranks first in every health service. The purpose of this study was to determine the description of age and gender in ARI cases in the Baula Health Center working area. This study used a research method with an observational design, and retrospective data collection. Data analysis using SPSS was descriptively conducted at the Baula Health Center surveillance installation in 2024. The highest cases were in 2023 as many as 737 patient visits with a diagnosis of ARI disease, and in 2022 as many as 527 visits. The results showed that there was a significant increase in the number of cases from 2022 to 2023. In the age group of 20-44 years, 64,5%, 45-54 years by 22,5%, the lowest in the age group of 60-69 years by 6.4% of the total 1,264 research samples.  In terms of gender, the most commonly diagnosed ARI was female at 66.9% and male at 33,1%. The study showed that the most diagnosed adult age of ARI cases was age 20-44 years, which amounted to 64,5% and in the most gender, women were more diagnosed with ARI than men, which amounted to 66,9%, finding that women are more susceptible to disease and want to get treatment immediately compared to men